Prosecutorial investigation: Pros and cons - Živković Natalija (Anali Pravnog Fakulteta u Beogradu, 2017)
Since 1890, Serbia had judicial investigation, but in 2011 a new law was brought. That was the way of transition from judicial to prosecutorial investigation. The author tried to find which of this two types of investigation is more efficient. By comparing pros and cons of judicial investigation and prosecutorial investigation author made a conclusion that prosecutorial investigation is more efficient than judicial investigation. Prosecutorial investigation provides possibility to the court to concentrate on his basic function-judgement. It also provides possibility to the prosecutor to research more than he could in judicial investigation. Prosecutorial investigation proclaims prosecutor as unbiased party in criminal procedure. It also obligates him to collect proofs at the expense and in favor of the defendant and that is problem. In addition to the analysis of the advantages and disadvantages of the judicial investigation and prosecutorial investigation author also presented features of the prosecutorial investigation under the Serbian Criminal Procedure Code from 2011.and the problems that arise there.